I. A. Karabinov’s liturgical studies as seen in the present-day perspective - Zoya Dashevskaya (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article studies I. A. Karabinov’s ideas and conceptions of forming the Eucharistic prayer presented in his thesis Eucharistic Prayer (Anaphora): An Attempt at Historical and Liturgical Analysis as well as in his course of lectures taught in the 1910s. This article analyses Karabinov’s views on the formation of the structure of the Eucharistic prayer, as well as the research methodology he used in studying the initial theological forms, the stages of development of the Eucharistic prayer and the interdependence of various liturgical traditions. Karabinov was the fi rst Russian scholar of liturgics to analyse the structure of the Eucharistic prayer sequence and to make use of the comparative method together with historical reconstructions, and without reliance on descriptions, commentaries and interpretations of earlier liturgical studies. He concludes that the Anaphora prayers which consisted of prayers of praise, thanksgiving and short intercessions, were later fi lled with words of exhortation, institution, dogmatic formulations and elaborated intercessions. These additional elements increased the volume of text in the Anaphora prayer, a situation which he believes led to a reduction of the prayer’s original elements, particularly the prayers of thanksgiving. Karabinov’s declared methodology opens the door to liturgical reconstructions which, nevertheless, will not be complete without consideration of the historical-theological context and church practice, neither of which were taken into account in Karabinov’s study. However, his approach of comparitive analysis makes it possible not to return to a moralising retelling of the Eucharistic prayer in narrow confessional confi nes, but allows one to study the text of the Eucharistic prayer in its development and to register all changes in its structure and content.